Evaluation of hydraulic mixing performance in a full-scale anaerobic digester with an external liquid recirculation system using CFD and experimental validation. (6th April 2022) - Arnau, Rosario; Climent, Javier; Martínez-Cuenca, Raúl; Rodríguez, Jorge; Chiva, Sergio
Graphical abstract: Highlights: CFD anaerobic digesters models were validated by means of complete RTD curve. Design mixing parameters in anaerobic digestion should be review. Local mixing parameters are strongly recommended for CFD studies. Second-order moments offer geometrical and local mixing information in CFD models. The propeller was found crucial to avoid dead volumes formation. Abstract: Anaerobic digestion (AD) has become an essential process for sludge treatment and its optimum performance is related to its mixing degree. In this study, a full-scale Anaerobic Digester (ADer) with an external recirculation mixing system was studied via single-phase 3D-CFD simulations to assess the influence of recirculation flow and a 3-blade propeller. The model was validated with inert tracer tests. The design and mixing parameters were studied to characterise the mixing efficiency in different scenarios. The design parameters were assessed first, but wide deviations from the recommended values were found. Local mixing parameters were found to be useful for defining the degree and type of mixing, and are highly recommended in the CFD studies of ADers. A second-order statistical moment was proposed as a global mixing parameter to describe geometrical and local mixing, and to state a reliable homogenisation time.